The Determinants of Foreign Direct Investment. An Empirical Study on China from 1999 to 2007 - Ma, Hong Mei (2008)
This paper examines the potential determinants of FDI on the country level from 1999 to 2007 by using Johansen-Juselius multivariate cointegration analysis and Granger causality test under Vector Error-correction model (VECM) framework. The findings of this study indicate that the labour cost, exchange rate and infrastructure development remained the important determinants of FDI in China for the period of 1999–2007. Besides, agglomeration effects have a significant impact on the new FDI. However, exchange rate becomes less significant in attracting inward foreign investments in China as compared with other factors. Surprisingly, the findings reveal that both the market size and its potential, and the degree of openness have insignificant effect on the inflows of FDI in China. The analysis of this study has important implications for Chinese government, during the time period that FDI is transformed from export orientated to market orientated. As Chinese labour cost gradually increases and the Yuan continues to revalue against the US dollar, the government should encourage capital-intensive FDI through the further development of skilled workforce and infrastructure. In addition, due to the significant impact of agglomeration effects on the inward FDI, instead of randomly allocating fiscal support to other aspects, giving preferences to focal cities that have the potential to develop as regional or national industrial cores, for example, the south-eastern coastal areas in China, could be more effective in attracting new FDI in the long run. Overall, the continuing endeavor to improve overall FDI-friendly environment of China is a longterm strategy